Hubungan Kecerdasan Emosional Terhadap Ketepatan Smash Atlet Bulutangkis - Pramudya Firdaus, Diva; Sudirjo, Encep; Ali Rahman, Aam (Universitas Hamzanwadi, 2024)
This research is important because it aims to examine the description of emotional intelligence and smash accuracy of PB Megantara badminton athletes. In this study, researchers used quantitative methods with a correlational research design. The population used in this study is the PB Megantara badminton club which totalled 30. The sample taken was 30 PB Megantara athletes with the sample technique used, namely total sampling. So that with this research it will be proven whether there is a relationship between emotional intelligence and the accuracy of smash badminton athletes. In this study, the instrument used was a questionnaire regarding emotional intelligence and for smash accuracy using the smash accuracy test. The results of data analysis are assisted by the SPSS21 application. Based on the results of the study, that there is a relationship between emocial intelligence on smash accuracy in badminton athletes which is calculated using a correlation test with significant results, namely (0.210)> (0.05), then a linearity test is carried out with the results of the r table (0.002) < (0.05) with the conclusion that there is a significant influence between smash accuracy and emotional intelligence in badminton athletes.